Yoga and music intervention reduces inattention, hyperactivity/impulsivity, and oppositional defiant disorder in children’s consumer with comorbid ADHD and ODD - Xue Luo; Xue Luo; Xu Huang; Shuang Lin (Frontiers in Psychology, 2023)
IntroductionTo analyze the impact of yoga and music intervention on child consumers, we selected 60 eligible child consumers from yoga and music companies.MethodsThis preliminary study used a randomized controlled design to investigate whether a 16-week combined yoga and music intervention improves attention, hyperactivity/impulsivity, and oppositional defiant disorder (ODD) in 60 children with attention-deficit/hyperactivity disorder (ADHD) comorbid with ODD aged 4–6 years. It also preliminarily identified which intervention is best for these children among three types: combined yoga and music, yoga-only, and musiconly interventions. We used both the parent- and teacher-rated MTA SNAP-IV ADHD Rating Scale for data collection.ResultsWe found that the combined yoga and music intervention had a positive effect on inattention, hyperactivity/impulsivity, and ODD in children with comorbid ADHD and ODD. The combined yoga and music intervention was the most effective in reducing inattention (in repeated measures ANOVA effect size, 0.9; followed by the yoga- and the music-only interventions, respectively), hyperactivity/impulsivity (effect size, 0.92), and ODD behaviors (effect size, 0.93) in children with comorbid ADHD and ODD. Thus, the combined yoga and music intervention was the most effective and had a more comprehensive effect on children with combined ADHD and ODD compared with the two other interventions (i.e., yoga- and music-only interventions).DiscussionOur findings provide preliminary evidence for the use of combined yoga and music interventions on a daily basis as a safe and effective adjunctive treatment for children with comorbid ADHD and ODD. The children in the article refer to child consumers of yoga and music companies.